Using Inquiry Based Learning Strategy in Teaching Writing Descriptive Text - Mike Amelia; Nostalgianti Citra Prystiananta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aimed to look at the effect of inquiry based learning strategy on students’ ability to write a descriptive text. The method of this research was quasi-experiment. The population of this research was eighth-grade students of MTsN Kota Solok. The total population was 65 students. The research results show that the pre-test means score in experimental and control classes was 46,8 and 44,4. The mean score of post-test in the experimental class was 55 and control class 51,6. Students’ ability in writing descriptive text analyzed by using t-test statistical which t calculated= 2,04 and t table (0,975: 38) = 2,02 with significant level t calculated > t table. In conclusion, the students who were taught using an Inquiry based learning strategy have better results in writing descriptive text than those who were taught without inquiry based learning. Keywords: Descriptive text, Inquiry Based Learning, Writing